Small intestine contrast ultrasonography for the detection and assessment of Crohn disease: A meta-analysis. Issue 31 (August 2016) - Zhu, Chenjing; Ma, Xuelei; Xue, Luqi; Xu, Jing; Li, Qingfang; Wang, Yun; Zhang, Jing
Abstract: Background: Crohn disease (CD) is a chronic relapsing disease. Imaging modalities are essential for the diagnosis and assessment of CD. Small intestine contrast ultrasonography (SICUS) is a well-tolerated, noninvasive and radiation-free modality and has shown potential in CD assessment. We aimed at evaluating the diagnostic accuracy of SICUS in the detection and assessment of small-bowel lesions and complications in CD. Methods: We searched PubMed database for relevant studies published before April 24, 2016. We integrated the true positive, false positive, false negative, and true negative into the pooled estimates of sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio. Forest plots were to represent the pooled results of all studies. Results: Thirteen articles were finally considered eligible. The pooled sensitivity and specificity of SICUS in detecting small-bowel lesions were 0.883 (95% confidence interval (CI) 0.847–0.913) and 0.861 (95% CI 0.828–0.890), respectively. The pooled diagnostic odds ratio was 39.123 (95% CI 20.014–76.476) and the area under the curve of summary receiver operating characteristic was 0.9273 (standard error: 0.0152). In subgroup analyses, SICUS represented fine sensitivity and specificity in proximal and distal small intestine lesion, as well as in CD-related complications such as stricture, dilation, abscess, and fistula. Conclusion: SICUS is accurate enough to make a complete assessment about the location, extent, number, and almost all kinds of complications in CD small-bowel lesions.